Place matters : gendered geography in Victorian women's travel books about Southeast Asia - Morgan, Susan, 1943- (Rutgers University Press, 1996)
"Susan Morgan's study of materials and regions previously neglected in contemporary postcolonial studies begins with the transforming premise that "place matters." Concepts derived from writings about one area of the world cannot simply be transposed to another area, in some sort of global theoretical move. Moreover, place in the discourse of Victorian imperialism is a matter of gendered as well as geographic terms. Taking up works by Anna Forbes and Marianne North on the Malay Archipelago, by Margaret Brooke and Harriette McDougall on Sarawak, by Isabella Bird and Emily Innes on British Malaya, by Anna Leonowens on Siam, Morgan also makes extensive use of theorists whose work on imperialism in Southeast Asia is unfamiliar to most American academics." "This vivid examination of a different region and different writings emphasizes that in Victorian literature there was no monolithic imperialist location, authorial or geographic. The very notion of a "colony" or an "imperial presence" in Southeast Asia is problematic. Morgan is concerned with marking the intersections of particular Victorian imperial histories and constructions of subjectivity. She argues that specific places in Southeast Asia have distinctive, and differing, masculine imperial rhetorics. It is within these specific rhetorical contexts that women's writings, including their moments of critique, can be read."--Jacket